The reflexive relationship between available university services and mental health ideations: A complexity informed perspective - Watson, Jacob; Lee, Taylor; Handayani, Sri (Frontiers in Communication, 2022)
Using Communication Complex as our theoretical framework, we explored socially constructed notions about mental health from a complexity informed perspective. Through qualitative interviews we investigated the availability of mental health services provided at three universities– one in Wrocław, Poland; one in Semarang, Indonesia; and the third in Indianapolis, Indiana, United States. From our interviews we interpreted several salient themes across all three cultures. Discussions about mental health services are meaningless without first defining mental health in pursuit of ascertaining what counts as caring for one’s mental health– a process which raises a host of epistemological and ontological questions in both the academic setting and the larger social milieu. These conversations also reified the importance of considering one’s whole health, how stigma plays a role in defining mental health “issues”, and what stories are being told about the nature of mental health across several cultures. We argue that there is a deeper, reflexive relationship between the ways people talk about mental health and what services are offered that goes beyond traditional notions of what mental health “is” and what counts as a mental health service.